Central and South-East European Resources in META-SHARE - Váradi, Tamás; Tadić, Marko (2012)
The purpose of this demo is to introduce the Language Resources, Tools and Services (LRTS) that are being prepared within the Central and South-East European Resources (CESAR) project. To the computational linguistic community the languages covered by CESAR (Bulgarian, Croatian, Hungarian, Polish, Serbian and Slovakian) were so far considered under-resourced and their language resources and tools being insufficient or hard to obtain, with limited coverage and processing capabilities. The CESAR project, functioning as an integral part of META-NET initiative, aims to change this situation by coordinating all relevant national stakeholders, to enlarge and enhance the existing LRTSs, as well as connect them multi-lingually in various ways. The most important aim of the project is to make all LRTSs for respective languages accessible on-line through the common European LRTS distribution platform META-SHARE. This demo will present how this platform can be used in different scenarios and how researchers or industry partners can easily access CESAR Language Resources, Tools and Services.
Projekt MZOS
ENG